Potential Antioxidant Activity of New Tetracyclic and Pentacyclic Nonlinear Phenothiazine Derivatives - Godwill Azeh Engwa; Eugene Lekem Ayuk; Benardeth Ujunwa Igbojekwe; Marcellus Unaegbu (Biochemistry Research International)
The global increase in oxidative stress related diseases such as cancer, cardiovascular, and inflammatory diseases caused by overwhelming level of free radicals in the body has encouraged the search for new antioxidant agents. Based on the ability of newly synthesized phenothiazine derivatives (6-chloro-11-azabenzo[a]phenothiazine-5-one and 6-[4-bromophenyl]-10-methyl-11-azabenzo[a]phenothiazine-5-one) to oxidize H2O2, a known free radical to sulfoxide, this study assessed the in vitro and in vivo antioxidant activity. The synthesized phenothiazine derivatives exhibited reducing power potential to convert Fe3+ to Fe2+ and high ability to scavenge H2O2 free radical in vitro. These activities were comparable to ascorbic acid, a standard antioxidant. The catalase activity significantly increased (p<0.05) in groups 1 and 2 animals that received the phenothiazine derivatives compared to the controls (groups 3 and 4) suggesting the ability of the phenothiazine derivatives to scavenge H2O2 in vivo. The malondialdehyde level in groups 1 and 2 animals was lower than that in group 3 that received the reference compound (ascorbic acid) and group 4 that received the solvent suggesting the ability of the phenothiazine derivatives to prevent lipid membrane damage. AST and bilirubin levels were higher in group 2 animals which received 6-[4-bromophenyl]-10-methyl-11-azabenzo[a]phenothiazine-5-one compared to group 3, the positive control. The results suggest that phenothiazine derivatives, especially 6-chloro-11-azabenzo[a]phenothiazine-5-one, possess antioxidant activity though 6-[4-bromophenyl]-10-methyl-11-azabenzo[a]phenothiazine-5-one was slightly toxic. This activity may be due to the presence of electron donors such as sulfur as well as the richness of hydrogen in the additional benzene rings for substitution. Further study is needed to identify tolerable doses for possible therapeutic purposes.